Fire alarm system using GSM / Muhammad Hanif Hasbullah - Hasbullah, Muhammad Hanif (2016)
The purpose of this project is to develop a fire alarm system using GSM module. The gas sensor used in this project is MQ-2 which is detect the present LPG, smoke, methane, and etc. These sensors will detect the concentration of the gas according to the voltage output from the sensor. In order to make the sensors operate correctly, Arduino Uno was used as the microcontroller for the whole system. GSM module also attached to the microcontroller to give the ability to send an alert to the user mobile phone.